Teachers' use of technology in the teaching and learning of English language in urban and rural schools - a comparative survey - Goh, Chui King (Universiti Malaysia Sarawak, UNIMAS, 2002)
This study aimed to investigate the extent of the use of technology in urban and rural secondary schools and it also looked into the problems faced by the teachers in the urban and rural secondary schools.